Mitral regurgitation in hypertrophic cardiomyopathy. Non-invasive study by two dimensional Doppler echocardiography. Issue 6 (June 1983) - Kinoshita, N; Nimura, Y; Okamoto, M; Miyatake, K; Nagata, S; Sakakibara, H
Abstract : Mitral regurgitation and its haemodynamic features were investigated non-invasively in cases of hypertrophic cardiomyopathy by means of two dimensional Doppler echocardiography. There were 28 patients, 14 of whom showed systolic anterior motion (SAM) of the mitral echo; the other 14 did not. The following results were obtained. (1) Mitral regurgitation was detected by the Doppler technique in all cases with systolic anterior motion of the mitral echo and in half of those without it. (2) Doppler signals of mitral regurgitation started immediately after the first heart sound. (3) Mitral regurgitant flow was often distributed from the entire mitral orifice over the entire or the posterior half of the left atrium in the cases with systolic anterior motion. In the cases without systolic anterior motion the regurgitation was usually localised near the mitral orifice. These features differ from those of regurgitation usually seen in rheumatic mitral valve disease and idiopathic mitral valve prolapse. (4) The Doppler technique and left ventriculography were equally efficient in detecting mitral regurgitation. (5) The early systolic component of the murmur of hypertrophic myopathy is considered to result in the main from concomitant mitral regurgitation, but not from turbulent blood flow in the left ventricular outflow tract, so that in cases with mitral regurgitation as a complication, mitral regurgitation may also contribute to the development of the midsystolic portion of the systolic murmur, while the main origin of this portion of the murmur is the left ventricular outflow obstruction.